IN-HOSPITAL BLOOD PRESSURE VARIABILITY AS A PREDICTOR OF LONG-TERM CARDIOVASCULAR MORTALITY IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION: ONE-YEAR FOLLOW-UP STUDY. (April 2021) - Konstantinou, K.; Tsioufis, K.; Koumelli, A.; Mantzouranis, M.; Kolokathis, K.; Milkas, A.; Fragoulis, C.; Kalos, T.; Andrikou, I.; Kasiakogias, A.; Dimitriadis, K.; Thomopoulos, K.; et al.
Abstract: Objective: The impact of blood pressure variability (BPV) on cardiovascular morbidity and mortality has been examined through the prism of heart failure and hypertension, but not in the setting of myocardial infarction (MI). The aim of this study is to determine the association between in-hospital short-term BPV and long-term cardiovascular outcomes in MI patients. Design and method: A total population of 260 patients (82.2% male; mean age: 63.8 years;71.3% hypertensives, 48.1% STEMI)underwent 24-hambulatory BP measurement during hospitalization for MI. At one year a follow-up was scheduled in order to assesscardiovascular mortality. The parameters of BPV analyzed were: a) 24-h standard deviation (SD), b) the coefficient of variation (CV) and c) the average real variability (ARV) of systolic and diastolic BP. Results: Cardiovascular death was independently predicted by SD SBP (HR = 2.406; 95% CI: 0.865–3.947; P = 0.002)and CV SBP (HR = 3.093; 95% CI: 1.833–4.354; P < 0.001) in the entire population and separately in STEMI group[(HR = 5.485; 95% CI: 2.958–8.012; P < 0.001) and (HR = 5.521; 95% CI: 3.230–7.813; P < 0.001) respectively]but not in the NSTEMI one. ARV failed to predict mortality in either group or the entire population. Multivariate regression models were conducted for both SD SBP and CV SBP in the STEMI group, in which, both remained potent predictors of cardiovascular mortality independently ofgender, age, hypertension, DM, smoking, low density lipoprotein (LDL-C) andGFR[(HR = 6.131; 95% CI: 3.716–8.546; P < 0.001) and (HR = 5.870; 95% CI:3.609–8.131; P < 0.001) respectively]. Conclusions: In the setting of MI, in-hospital BPV was associated with cardiovascular mortality during the one-year follow-up. These findingscould suggest a clinical need for further individualization of BP regulation in the integrative ACS management.